A modified metabolic model for mixed culture fermentation with energy conserving electron bifurcation reaction and metabolite transport energy1. Issue 7 (22nd February 2013) - Zhang, Fang; Zhang, Yan; Chen, Man; van Loosdrecht, Mark C.M.; Zeng, Raymond J.
Abstract A modified metabolic model for mixed culture fermentation (MCF) is proposed with the consideration of an energy conserving electron bifurcation reaction and the transport energy of metabolites. The production of H2 related to NADH/NAD+ and Fdred/Fdox is proposed to be divided in three processes in view of energy conserving electron bifurcation reaction. This assumption could fine‐tune the intracellular redox balance and regulate the distribution of metabolites. With respect to metabolite transport energy, the proton motive force is considered to be constant, while the transport rate coefficient is proposed to be proportional to the octanol–water partition coefficient. The modeling results for a glucose fermentation in a continuous stirred tank reactor show that the metabolite distribution is consistent with the literature: (1) acetate, butyrate, and ethanol are main products at acidic pH, while the production shifts to acetate and propionate at neutral and alkali pH; (2) the main products acetate, ethanol, and butyrate shift to ethanol at higher glucose concentration; (3) the changes for acetate and butyrate are following an increasing hydrogen partial pressure. The findings demonstrate that our modified model is more realistic than previous proposed model concepts. It also indicates that inclusion of an energy conserving electron bifurcation reaction and metabolite transport energy for MCF is sound in the viewpoint of biochemistry and physiology. Biotechnol. Bioeng. 2013; 110: 1884–1894. © 2013 Wiley Periodicals, Inc.